2004
DOI: 10.1186/1741-7015-2-14
|View full text |Cite
|
Sign up to set email alerts
|

Parasomnias and sleep disordered breathing in Caucasian and Hispanic children – the Tucson children's assessment of sleep apnea study

Abstract: Background: Recent studies in children have demonstrated that frequent occurrence of parasomnias is related to increased sleep disruption, mental disorders, physical harm, sleep disordered breathing, and parental duress. Although there have been several cross-sectional and clinical studies of parasomnias in children, there have been no large, population-based studies using full polysomnography to examine the association between parasomnias and sleep disordered breathing. The Tucson Children's Assessment of Sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
2
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 46 publications
3
85
2
9
Order By: Relevance
“…Thus, a major bias related to test-re-test reliability is unlikely in the present study. The participation rate is similar to that reported previously in a population-based cohort study [9], and higher than those reported in previous follow-up [22] and cross-sectional studies [23]. This is an important strength of the present study because long time intervals have generally been negatively related to response rates [24].…”
Section: Discussionsupporting
confidence: 65%
“…Thus, a major bias related to test-re-test reliability is unlikely in the present study. The participation rate is similar to that reported previously in a population-based cohort study [9], and higher than those reported in previous follow-up [22] and cross-sectional studies [23]. This is an important strength of the present study because long time intervals have generally been negatively related to response rates [24].…”
Section: Discussionsupporting
confidence: 65%
“…Consecutive children who underwent tonsillectomy for either OSA or RI were identified before surgery and recruited into the study. The diagnosis of OSA syndrome was established by overnight polysomnography in the sleep laboratory and required the presence of apnea-hypopnea index Ͼ5 events/h of sleep (23). Patients who were referred for RI were selected on the basis of a history of at least five tonsillar infections in Ͻ6 mo, and because the absence of any symptoms suggestive of OSA essentially negates the presence of this condition (11), they were not evaluated by an overnight polysomnogram, because our questionnaire-based evaluation is highly sensitive and specific in ruling out sleep-disordered breathing in children (11).…”
Section: Methodsmentioning
confidence: 99%
“…Morbidity from the central nervous system a) The association between excessive daytime sleepiness and OSAS is supported mainly by studies of low methodological quality (class IV) [90][91][92][93]. Few studies have employed multiple sleep latency tests (class I and III) [94][95][96].…”
Section: Literature Reviewmentioning
confidence: 99%